The The Correlation between Tuberculous Lymphadenitis and Nutritional Status in Children - Muhammad Ali Shodikin; Ika Rahmawati Sutejo; Yasmin Auralia Putri (Universitas Nahdlatul Ulama Surabaya, 2022)
Tuberculous lymphadenitis may cause weight loss and lead to malnutrition in children.This study analyzes the correlation between tuberculous lymphadenitis and nutritionalstatus in children. It was an analytic observational study with a cross-sectional design.The population was pediatric patients under 18 years old with lymphadenitis, outpatientand inpatient admitted from January 2018 to December 2020 in dr. Soebandi publichospital, Jember, Indonesia. The samples were 76 respondents with total sampling. There were 52 tuberculosis lymphadenitis patients in the case group, while 24 were non-tuberculosis in the control group. The body weight data was from the medical record when the first diagnosis of lymphadenitis. Instruments were weight-for-age z-scorecurves (WHO, 2007) for under 60 months old children, while CDC Growth Charts 2000for more than five-year-old children. Then, data analysis used the Chi-square test.Mostly, tuberculous lymphadenitis patients were girls (65.4%), 12-17 years old (67.3%),not underweight (61.5%), and lived in rural areas (73%). Furthermore, all of them weregiven isoniazid, rifampicin, and pyrazinamide. In addition, 100% of them had successfultreatment. Meanwhile, most of the non-tuberculous lymphadenitis patients were boys(54.2%), 6-11 years old (58.3%), lived in the rural areas (79%), and were notunderweight (66.7%). Treatment of the non-tuberculous lymphadenitis group consistedof antibiotics, analgesics, vitamins, and symptomatic medicine. The Chi-square testresults obtained p=0.667 (p>0.05). In conclusion, tuberculosis lymphadenitis in theearly incubation period